CURENT CONCEPT OF MORPHOFUNCTIONAL CHANGES OF DENTAL TISSUE INDUCED BY ODONTOPREPARATION FOR METAL-CERAMIC CONSTRUCTIONS - Hasiuk, N.V.; Hasiuk, P.A.; Radchuk, V.B. (World of Medicine and Biology, 2017)
Progressive development of modern stomatological science involves the continuous improvement of the known methods of diagnosis and treatment of dental diseases. In the field of prosthodontics example of this trend is the availability of metal-free crowns in the market, which have appeared as an alternative to metal-ceramic. However, taking into account the number of factors metal constructions are still relevant. Basing on the analysis of the literature to optimize approach in odontopreparation for metal-ceramic crowns, identify morphological changes of dental tissues at different types of orthodontic preparation, and give clinic-morphological study of the proposed method of preparing teeth for metal-ceramic construction. Analytical method based on analysis of histochemical, histological features of identifying structural components of hard tissue in intact teeth and teeth with different types of odontopreparation and volumetric digital scanning to determine the working preparation thickness of hard tooth tissue in different experimental groups. Analyzing the literature, the results of own research it should be affirmed the development of some kind of vibration disease in the tissues of the tooth that causes destructive changes of hard tissue and pulp, expressed in varying degrees in experimental groups. On the basis of the determined morphological changes in the tissue of teeth during odontopreparation for metal-ceramic construction, it is justified the maximum preservation of hard tissue of neck area, forming a ledge symbol, to maximize the functional capacity of the pulp, which is confirmed by a number of own laboratory research.
Keywords: orthodontic preparation; metal-ceramic crowns; morphofunctional changes in dental tissues; CAD / CAM